Clinical Care Tracker: a new member of community Specialist Palliative Care team. Issue 2 (1st June 2012) - Hayes, J.; Nelson, A.; Harry, K.; Hayles, L.; Byrne, A.; Stephens, K.
Abstract : Introduction: The Clinical Care Tracker (CT) role has been established to enhance the quality and efficiency of services provided by the Community Specialist Palliative Care Team (CSPCT) at Marie Curie Hospice, Penarth. The CT is a Registered Nurse who works exclusively on the telephone, providing a point of contact for any patient or family on the CNS caseload and for clinicians and services involved in their care. The team implemented a traffic light system for stratifying the community specialist palliative care caseload and the 'green' patients are monitored by the CT. Aims & Methods: To provide stable patients and their carers with regular contact, support or self-care information. To monitor for change in clinical status or indication of likely deterioration, prompting immediate increased input from CSPCT. For patients who are in crisis, the CT enables a rapid assessment of their needs and escalation to the relevant care to ensure the patients' needs are met. To supplement the face to face support provided by the CSPCT team. This is an innovative approach based on the Croydon model of a virtual ward in the community (Lewis, 2006) and the Department of Health model of a care tracker for chronic conditions (Player, 2007). Evaluation has been undertaken using a variety of sources including focus groups, observation, semi-structured interviews, impromptu interviews, attendance at weekly multi-disciplinary meeting and analysis of activity data. Results: The evaluation highlighted a risk that palliative care patients who are not receiving regular input from the Specialist Palliative Care CNS can get lost in the complex system of care. This is of particular relevance when they have a lower level of need, but are likely to deteriorate in the future. The Care Tracker offers a more appropriate way of stepping down the intensity of the support and giving the patient more choice about how much they engage with the service. Conclusion: The care tracker provides a way to monitor patients and enable the CNS team to intervene in a timely way if the patient deteriorates and their needs become more complex.